Adaptive pseudo‐linear control for grid‐supportive PV system. Issue 9 (12th April 2019) - Kumar, Shailendra; Jain, Chinmay; Singh, Bhim
Abstract : This work demonstrates a grid‐supportive photovoltaic (PV) system with an adaptive pseudo‐linear control. The proposed PV system utilises a boost converter and a voltage source converter (VSC). The VSC performs multitasks such as load balancing, harmonics suppression and enhancing active power penetration to the grid. Wherein, a perturb and observe based technique serves the function of maximum power point tracking through the control of a boost converter. However, an adaptive pseudo‐linear control is used for control of VSC. The adaptive pseudo‐linear algorithm is used for the evaluation of fundamental components of load currents and it estimates the reference grid currents. The grid currents are controlled to generate the insulated gate bipolar transistors firing signals for VSC. A prototype of PV system is developed in the laboratory and implemented under different loads and solar insolation levels. The total harmonic distortions of grid currents are preserved within the limits in accordance with the IEEE‐519 standard.